De Novo Sequencing of a Sparassis latifolia Genome and Its Associated Comparative Analyses - Donglai Xiao; Lu Ma; Chi Yang; Zhenghe Ying; Xiaoling Jiang; Yan-quan Lin (Canadian Journal of Infectious Diseases and Medical Microbiology)
Known to be rich in β-glucan, Sparassis latifolia (S. latifolia) is a valuable edible fungus cultivated in East Asia. A few studies have suggested that S. latifolia is effective on antidiabetic, antihypertension, antitumor, and antiallergen medications. However, it is still unclear genetically why the fungus has these medical effects, which has become a key bottleneck for its further applications. To provide a better understanding of this fungus, we sequenced its whole genome, which has a total size of 48.13 megabases (Mb) and contains 12,471 predicted gene models. We then performed comparative and phylogenetic analyses, which indicate that S. latifolia is closely related to a few species in the antrodia clade including Fomitopsis pinicola, Wolfiporia cocos, Postia placenta, and Antrodia sinuosa. Finally, we annotated the predicted genes. Interestingly, the S. latifolia genome encodes most enzymes involved in carbohydrate and glycoconjugate metabolism and is also enriched in genes encoding enzymes critical to secondary metabolite biosynthesis and involved in indole, terpene, and type I polyketide pathways. As a conclusion, the genome content of S. latifolia sheds light on its genetic basis of the reported medicinal properties and could also be used as a reference genome for comparative studies on fungi.